The Effect of Closed Wheels on Efficiency and Losses - Zaka Nurfadilah; Dan Mugisidi; Abdul Rahman Soleh Pohan; Oktarina Heriyani (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
Waterwheel is a component in a Micro Hydro Power Plant (PLTMH) which obtains energy from flowing water which has a height and speed. The amount of energy converted by the water wheel depends on the shape of the blade and the installation position, but the losses due to wasted water are still large. Therefore this study proposes a closed water wheel to reduce losses. This research uses two condition fo water wheel: open wheel and closed wheel. This research uses one mill which applied into two conditions. The waterwheel is made using Polylactid Acid (PLA)and tested using 2 inch pipe lines and flow rates of 10, 12, 14, 16, 18, 20 m3/hour. The efficiency of a closed water wheel is higher than that of an open wheel at all discharge rates. The highest efficiency for a closed wheel is 54.54% and for an open wheel is 52.25% at a discharge of 10 m3/hour with a loss ratio of 0.078 for an open wheel and 0.065 for a closed wheel which shows that the losses in the water wheel are reduced.